CGMP Signaling in Cardiovascular Diseases: Linking Genotype and Phenotype. Issue 6 (June 2020) - Dang, Tan An; Schunkert, Heribert; Kessler, Thorsten
Abstract : Abstract: Cyclic guanosine 3′, 5′-monophosphate (cGMP) is the key second messenger molecule in nitric oxide signaling. Its rapid generation and fate, but also its role in mediating acute cellular functions has been extensively studied. In the past years, genetic studies suggested an important role for cGMP in affecting the risk of chronic cardiovascular diseases, for example, coronary artery disease and myocardial infarction. Here, we review the role of cGMP in atherosclerosis and other cardiovascular diseases and discuss recent genetic findings and identified mechanisms. Finally, we highlight open questions and promising research topics.